INTEGRATING SPATIAL MAPPING AND SOCIO-CULTURAL DYNAMICS FOR SUSTAINABLE ECOTOURISM MANAGEMENT AT GOA ERGENDANG: A GEO-ANTHROPOLOGICAL STUDY IN DELI SERDANG REGENCY - Mita Nalsalisa Br Barus; Vadillah Raihto Hutasuhut; Muhammad Najmul Fahmi; Angelo Arevalo Simanullang; Annisa Oktavira; M Faoug Ghazali Matondang (Geographica: Science and Education Journal, 2025)
Goa Ergendang, a unique geo-cultural site in Deli Serdang, Indonesia, possesses significant ecotourism potential, including natural hot springs, stalactites, and rich local folklore (the Umang mythos). However, its development is severely hindered by informal community self-management, poor infrastructure, and a critical lack of spatial information for visitors. This research aims to (1) identify the fundamental challenges in its sustainable management and (2) formulate an integrated management model based on a geo-anthropological approach. This study employed a mixed-method design, integrating quantitative spatial analysis (GIS) with qualitative socio-cultural analysis. Methods included GIS mapping for accessibility, topography, and potential zoning, combined with in-depth interviews with local managers, stakeholders, and visitors. The findings reveal four primary challenges: (1) weak institutional capacity due to informal management, leading to resource limitations and poor heritage protection (e.g., the destruction of the "sacred drum stone"); (2) severe  infrastructural barriers, particularly damaged access roads; (3) a critical spatial information gap, evidenced by 16 hidden pools remaining unknown to visitors due to a lack of maps; and (4) high physical vulnerability from steep topography and corrosive acidic water. This research proposes a sustainable management model based on Community-Based Ecotourism (CBT) supported by GIS planning. In this model, GIS functions as the objective physical planning tool for conservation zoning and visitor navigation, while a formalized community institution (e.g., BUMDes/Village-Owned Enterprise) acts as the socio-cultural manager, responsible for revitalizing local culture (Ergendang and Umang myths) as a core attraction. This integrated geo-anthropological model provides a clear pathway to optimize the area's unique potential sustainably.